Communicating Process Architectures 2008 WoTUG-31 - Welch, Peter H (IOS Press, 2013)
The thirty-first Communicating Process Architectures Conference, CPA 2008, organised under the auspices of WoTUG and the Department of Computer Science of the University of York, is being held in York, UK, 7–10 September 2008. The York Department of Computer Science is delighted to host this conference again. The thirteenth Occam User Group Technical Meeting (from which these CPA conferences are descended) on “Real-Time Systems with Transputers” was held at this University in September, 1990. York has a long history of close contacts with this conference, from the early heady days when occam was new, to current collaborations with the University of Kent using occam-π for simulating complex systems. The satellite workshop “Complex Systems Modelling and Simulation (CoSMoS)”, arising from this collaboration, is part of this year’s conference.